Penerapan Algoritma Dijkstra dalam Pendistribusian Paket Permakanan Bagi Lansia Tunggal dan Penyandang Disabilitas Tunggal di Kelurahan Klampok Kota Blitar - Fayaqun, Reza (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Ministry of Social Affairs presents a national program as an effort to respect, protect and guarantee social security in the form of fulfilling food and nutritional needs known as the Food Social Assistance Program. This program is intended for single elderly and single disabled people with assistance for two meals per day with the aim of empowering the community and helping single elderly and single disabled people in meeting their decent standard of living. Distribution is centered on the sub-districts of each region throughout Indonesia, one of which is Klampok sub-district, Sananwetan district, Blitar City. In the distribution of this assistance, there are 23 heads of families who are eligible for assistance spread across several locations, this becomes a problem if the order of food distribution is carried out randomly without prioritizing distance and delivery time. The method used to solve this problem is the Dijkstra algorithm for determining the shortest route because it can determine the shortest route from a weighted graph where the weight is greater than zero (positive), from the starting point of all desired points, so that the shortest route can be found from the starting point to the destination point. The calculation results of the Dijkstra algorithm produce a sequence of each food package distribution point starting from node A-E-B-C-D-F-I-H-J-G-K-N-M-O-L-Q-P-R-S-T-U-V-W-X where this sequence covers a distance of 3,883 meters or 3.883 km.